Resource trading in cloud environments for utility maximisation using game theoretic modelling approach. Issue 4 (3rd July 2016) - Alsarhan, Ayoub; Al-Khasawneh, Ahmad
Abstract : We develop a novel auction-based scheme for trading free processors in cloud computing environment. Our scheme allows clients to fairly compete for the offered processors. Second-price auction is used where each client bids for the processors. The client that makes the higher bid wins the auction and starts using the processors for executing its jobs. The winner pays the second highest bid. Maximising profit is the key objective for the cloud provider (CP). The optimisation problem of renting processors on the cloud market is a complex and challenging task. The proposed mechanism takes into account the market demand and the economic concerns for the CP and clients. Within this context, we show the existence of a Nash equilibrium which leads to a unique allocation under certain processors distribution. Numerical analysis stresses the ability of our approach to maximise the client's utility under varying cloud environment conditions.